Collateral Damage - Alexander, Hannah (Thorndike, Maine : Center Point Large Print, 2015)
"Long-buried secrets will come to light as Sarah Russell and Nick Tyler look into the explosion that took the lives of her parents and his mother in Jolly Mill, Missouri. After two more deaths occur, they will need to solve the murders before someone else close to them becomes a casualty"--
Keywords: Large type books; Romantic suspense fiction